Disturbing revelation: Leo Strauss, Eric Voegelin, and the Bible - Ranieri, John J. (University of Missouri Press, 2009)
"Ranieri shows how Leo Strauss and Eric Voegelin drew on biblical texts in their philosophies to explore the relationship between religion, politics, and violence while maintaining a deep ambivalence about the Bible's vision of life and its influence on politics and finally compares their thought with that of René Girard"--Provided by publisher